2012
DOI: 10.4070/kcj.2012.42.5.329
|View full text |Cite
|
Sign up to set email alerts
|

The Number of Endothelial Progenitor Cells is Decreased in Patients With Non-Dipper Hypertension

Abstract: Background and ObjectivesCirculating endothelial progenitor cells (EPCs) play a key role in the maintenance of endothelial homeostasis and promote vascular repair. A reduced number of EPCs and the functional activity have been associated with several cardiovascular risk factors. However, the relationship between the number of EPCs and circadian rhythm of the blood pressure (BP) remains unclear. The purpose of the present study was to evaluate the relationship between the circadian rhythm of the BP and EPCs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…Nondipping nocturnal blood pressure is also associated with vascular endothelial dysfunction and reduced nitric oxide levels [36]. Furthermore, nocturnal nondippers demonstrate a reduced number of endothelial progenitor cells, which are responsible for repairing vascular damage and maintaining homeostasis [37], a finding also reported in patients with OSA [38].…”
mentioning
confidence: 56%
“…Nondipping nocturnal blood pressure is also associated with vascular endothelial dysfunction and reduced nitric oxide levels [36]. Furthermore, nocturnal nondippers demonstrate a reduced number of endothelial progenitor cells, which are responsible for repairing vascular damage and maintaining homeostasis [37], a finding also reported in patients with OSA [38].…”
mentioning
confidence: 56%
“…Non-dipper blood pressure pattern is associated with cardiovascular mortality, endorgan damage and autonomic dysfunction [13][14][15]. There is evidence that number of endothelial progenitor cells is decreased in hypertensive non-dipper status meaning vascular repair mechanisms and endothelial homeostasis is disturbed [16]. Elevated blood pressure and decreased blood pressure variability may stimulate inflammation by increased expression of endothelial cytokines [6].…”
Section: Discussionmentioning
confidence: 99%
“…Impaired endothelial function is associated with cardiovascular and cerebrovascular diseases, both of which are more prevalent in non-dipper HT patients [35]. Kim et al [36] reported that endothelial progenitor cells, which play a key role in endothelial homeostasis and vascular repair, are less prevalent in the circulation of nondipper than dipper HT patients. In addition, aortic stiffness, which increases with atherosclerosis and endothelial dysfunction [37], has been shown to be increased in non-dipper HT patients compared with dipper HT patients [38,39].…”
Section: Discussionmentioning
confidence: 99%